Mad Honey Intoxication: A Rare Case Report - Khakural, Raunak; Shrestha, Shailesh; Pandey, Kundan Raj; Gurung, Sanyukta (Nepal Journal of Health Sciences, 2022)
Honey containing grayanotoxin is called mad honey which is found in Turkey, Japan, Brazil, Europe, North America and Nepal. Patients present with clinical manifestations like bradycardia, hypotension and syncope. In this case report we present a 27 years male who presented with bradycardia and first-degree heart block after consumption of only 10 grams of mad honey.